Escalation of Anesthesia In Vitrectomy for Chronic Kidney Disease Patients: From Peribulbar Block to General Anesthesia - Ida Bagus Indrayoga Permana; I Made Gede Widnyana (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Patients with Stage V Chronic Kidney Disease (CKD) face a significantly higher risk of ocular pathologies, notably Tractional Retinal Detachment (TRD) resulting from proliferative diabetic retinopathy. Anesthetic management for these patients is complex due to impaired drug clearance, cardiovascular comorbidities (CHF, HHD), and the necessity for absolute ocular immobility during vitreoretinal surgery. Regional anesthesia is typically preferred to minimize systemic complications, though technical escalation may be required. A 43-year-old male with Stage V CKD on regular hemodialysis, CHF (FC II), and Type II Diabetes Mellitus was scheduled for a left eye vitrectomy. An initial peribulbar block (8 mL Lidocaine 2% and Bupivacaine 0.5%) resulted in partial akinesia (score 4/8). A rescue Sub-Tenon block successfully achieved total akinesia (score 0/8). However, intraoperative agitation necessitated propofol sedation, which led to oversedation and airway obstruction. Due to limited airway access during the procedure, the technique was escalated to general anesthesia. Induction utilized dose-adjusted fentanyl (75 mcg), propofol (100 mg), and atracurium (30 mg) to ensure renal-independent metabolism. The surgery proceeded with stable hemodynamics. A "deep" extubation was performed to prevent Valsalva-induced increases in intraocular pressure. The patient recovered well with an initial Aldrete score of 8/10. Peribulbar blocks are safer for uremic patients but success is volume-dependent and failure may require rescue techniques like Sub-Tenon blocks. When regional techniques and sedation fail or compromise the airway, conversion to general anesthesia is a necessary last resort. In CKD, the choice of agents and careful dose titration of opioids are critical to prevent prolonged respiratory depression and neuromuscular blockade. While regional anesthesia is the primary choice for fragile CKD patients, clinicians must remain prepared for technical escalation. Success in such cases depends on the timely conversion to general anesthesia using renal-independent agents and smooth emergence techniques to protect surgical outcomes. Keywords: Chronic Kidney Disease, General Anesthesia Conversion, Peribulbar Block, Vitrectomy.